The Chicken Pan-Genome Reveals Gene Content Variation and a Promoter Region Deletion in IGF2BP1 Affecting Body Size. (30th July 2021) - Wang, Kejun; Hu, Haifei; Tian, Yadong; Li, Jingyi; Scheben, Armin; Zhang, Chenxi; Li, Yiyi; Wu, Junfeng; Yang, Lan; Fan, Xuewei; Sun, Guirong; Li, Donghua; et al.
Abstract: Domestication and breeding have reshaped the genomic architecture of chicken, but the retention and loss of genomic elements during these evolutionary processes remain unclear. We present the first chicken pan-genome constructed using 664 individuals, which identified an additional approximately 66.5-Mb sequences that are absent from the reference genome (GRCg6a). The constructed pan-genome encoded 20, 491 predicated protein-coding genes, of which higher expression levels are observed in conserved genes relative to dispensable genes. Presence/absence variation (PAV) analyses demonstrated that gene PAV in chicken was shaped by selection, genetic drift, and hybridization. PAV-based genome-wide association studies identified numerous candidate mutations related to growth, carcass composition, meat quality, or physiological traits. Among them, a deletion in the promoter region of IGF2BP1 affecting chicken body size is reported, which is supported by functional studies and extra samples. This is the first time to report the causal variant of chicken body size quantitative trait locus located at chromosome 27 which was repeatedly reported. Therefore, the chicken pan-genome is a useful resource for biological discovery and breeding. It improves our understanding of chicken genome diversity and provides materials to unveil the evolution history of chicken domestication.